STUDENTS’ MOTIVATION AND PROBLEMS IN LEARNING ENGLISH IN EFFECTIVE ENGLISH CONVERSATION COURSE (EECC) - Sahril Mujani (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
This research is aimed to know students’ motivation and problems in learning English in Effective English Conversation Course (EECC). The design of this research was descriptive qulitative. The sample was 15 students. The research instruments in this research were tests and questionnaire. The results of finding showed that 1) students’ intrinsic motivation in learning was high namely 12 students (80%). 2) students’ extrinsic motivation in learning English was high namely 12 students (80%). 3) students’ problems in learning English were in listening skill (85%), reading skill (56%), and writing skill (57%) as category high. 4) students’ ability in learning English was 66 as category average. It is recommended that the teachers pay attention to the students’ motivation and problems in learning English because it influenced to the students’ ability.